Development of a novel 3-month drug releasing risperidone microspheres - Bhanusree Yerragunta; Satheesh Jogala; Krishna Mohan Chinnala; Jithan Aukunuru (Wolters Kluwer Medknow Publications, 2015)
Objective: The purpose of this study was to develop an ideal microsphere formulation of risperidone that would prolong the drug release for 3 months in vivo and avoid the need for co-administration of oral tablets. Materials and Methods Polycaprolactones (PCL) were used as polymers to prepare microspheres. The research included screening and optimizing of suitable commercial polymers of variable molecular weights: PCL-14000, PCL-45000, PCL-80000 or the blends of these polymers to prepare microspheres with zero-order drug-releasing properties without the lag phase. In the present study, the sustained release risperidone microspheres were prepared by o/w emulsion solvent evaporation technique and the yield was determined. Microspheres were evaluated for their drug content and in vitro drug release. Microspheres prepared using a blend of PCL-45000 and PCL-80000 at a ratio of 1:1 resulted in the release of the drug in a time frame of 90 days, demonstrated zero-order drug release without lag time and burst release. This formulation was considered optimized formulation. Optimized formulation was characterized for solid state of the drug using differential scanning calorimetry, surface morphology using scanning electron microscopy and in vivo drug release in rats. Results: The surface of the optimized formulation was smooth, and the drug changed its physical form in the presence of blends of polymers and upon fabrication of microspheres. The optimized formulation also released the drug in vivo for a period of 90 days. Conclusions: From our study, it was concluded that these optimized microspheres showed great potential for a better depot preparation than the marketed Risperdal Consta™ and, therefore, could further improve patient compliance.